Partitioning of Nitrogen in Grapevines during Autumn and the Utilisation of Nitrogen Reserves during the Following Growing Season - Conradie, W.J. (South African Journal of Enology and Viticulture, 2017)
The distribution and translocation of nitrogen (NJ absorbed during autumn (post-harvest) were quantified for twoyear-old Chenin blanc grapevines grown in sand culture. Vines were labelled with I SN over a one-month period immediately after harvest. From this stage onwards vines were fed unlabelled Hoagland solution. Selected vines were destructively sampled over a period of seven months, i.e. twice at the end of the second season (start of leaf-fall and end of leaf-fall) and three times at the start of the third growing season (bud break, before bloom and after bloom). Autumnabsorbed N accounted for 60% of the total amount of N-reserves present at the start of the third season. The utilisation of these N-reserves over the first part of the third season was compared to that of reserves originating from the previous spring and summer, respectively. All reserve pools were utilised equally with one quarter being translocated to new growth up to the end of bloom. At the latter stage one-year-old reserves accounted for at least 18% of the N-demand of the new growth. Newly absorbed N and reserve N were allocated to all the new organs in equal ratios. It was estimated that 50% of the N-reserves present at budbreak will be utilised up to harvest. After bloom, however, reserve N lost from the permanent structure was compensated for by newly absorbed N, which was not the case before bloom.